PENDIDIKAN KEPEMIMPINAN M. NATSIR DAN IMPLEMENTASINYA DI LEMBAGA PENDIDIKAN - Saiful Falah (Sekolah Tinggi Agama Islam Al Hidayah, 2015)
The situation worsened due to the Indonesian nation rampant cases of corruption committed by its leaders from central to local levels. Officials who belonged to well-educated should understand the meaning of leadership. Unfortunately they consider being a leader is an opportunity for personal gain. This happens because they do not have or have less education material about leadership. Generally school had been too focused on the students' cognitive self not accompanied by an increase in affective and psychomotor. Though both of these aspects is a great asset for a leader.This study aimed to find the exact model of educational leadership as a solution to the above problems. M. Natsir as a leader of the nation has given us an example of how to be leaders in a community. Therefore, his thoughts on leadership education can serve as a model for implementation in educational environments such as homes, schools and communities. The approach used in this study is library research. The research process begins with a search-related book titles, specify the primary sources written directly by M. Natsir and secondary sources of other people's work on M. Natsir. From those sourceswe found M. Natsirâ€™s thoughtaboutleadership education. Then the analysis is done and conclusions are drawn. The study also called qualitative research, therefore qualitative methods applied to use descriptive writing techniques. This research concludes that, M. Natsirâ€™s thought About Leadership Education is important for the implementation of leadership education for the younger generation. Models are offered by M. Natsir include; regeneration, assignment and example. All three models can be applied in three education centers; homes, schools and communities. With the implementation of the three models, the younger generation who will be the leaders of tomorrow can absorb leadership knowledge so they can grow as a genuine leader in the community.Â Keywords: Kepemimpinan, M. Natsir, Pendidikan